Pengaruh Pemberian Diazepam, Formalin dan Minuman Beralkohol terhadap Bobot Intestinum, Hepar dan Ren Mencit Mus musculus L. - Santosa, Titih Nurasri; Saraswati, Tyas Rini; Tana, Silvana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
The use of dangerous chemicals in society is inevitable, whether as a sedative, to preserve food or to lifestyle. This chemicals include of diazepam, formalin and alcohol. When it enters the body can change the objec cells that will affect the body’s physiological processes and the resulting changes in the organ weights. The reearch was aimed to determine the final weight of intestinum, liver, and ren mice based on the function of these organs in the digestive tract after administration of diazepam, formaline, and alcoholic beverages. The treatment of 16 adult male mice dan weighing around 25 – 30 grams for 30 day’s with a Completely Randomized Design Methods, divided into 4 treatment groups each of 4 replicates, which is group P1 (0,04 mg diazepam), P2 (formaline 100ppm), P3 (4,8 % alcohol) and P0 as control (destilled water). Data were analysed by ANOVA showed that there was not siqnificant difference in weight intestinum and ren, whereas the liver weight, so there is a noticeable difference LSD test followed by 95%. The results showed that the chemical compounds has not able disturb the function ren and intestine, but increased the activity of hepatic metabolism. Key word : diazepam, formaline, alcohol , intestine, ren and liver weight